How the Perception of Public Official on Organizational Culture Influences Procedural Justice in Environmental Policy Processes - Yuan, Meng (Frontiers in Psychology, 2021)
How does the organizational culture of local governments influence the type and extent of procedural justice in environmental policy processes? Using the culture theory developed by Mary Douglas and others, this research seeks to bring a new conception and new measures of organizational culture to the study of policy making by local governments. To contribute to the development of the conceptualization and measurement of procedural justice in the environmental policy processes of those governments, item response theory (IRT) graded response model (GRM) is used to show variations in difficulties and frequencies of adopting distinctive public participation strategies for improving procedural justice across local governments. In this study, original survey data is collected from Illinois municipalities and a finding is suggestive of cultural variables explaining the two dimensions of procedural justice, equal and authentic public participation, while other variables can, at best, explain only the equal public participation. Furthermore, as hypothesized, egalitarianism increases both equal and authentic public participation, individualism increases equal public participation, and fatalism decreases both.